Technology in the classroom as a pedagogical tool: a perspective by the view of students from an educational institution in Botucatu (SP) - Oliveira Gomes, Mike Ceriani de; Toledo Piza, Mariana Wagner de [UNESP] (Univ Nove Julho, 2020)
The main issue related to this article is the adherence to technologies in the classroom, focusing on the study of their good use. There is a theoretical explanation in which it is debated how the same process has been growing over the years, considering other technologies than Smartphones, which are on the rise in Brazil and around the world, being also very present in the classroom. To have a discussion of data, it was chosen the deductive methodology before a field research that took place in a vocational school of Botucatu (Sao Paulo State - Brazil). This research brought new expectations and contributions that come from the students' perspective to the modernization of the teaching environment and to the creation of opportunities for autonomy in the learning processes.
Keywords: New technologies; Teacher training; Autonomy